Training Ekiti Women for Economic Resilience at the Ekiti State Women Development Centre - Gladys Modupe Kayode; Mary Olufunke Adedokun; Oluwayemi Blessing Adegbola; M. Yoserizal Saragih (Budapest International Research and Critics University, 2020)
The use of the training facilities of the Ekiti State Women Development Centre to build economic resilience in Ekiti State women was examined. This was borne out of the need to boosts productivity, increases economic diversification, realizing gender and income equalities. Three sets of respondents – Women graduates of ESWDC, randomly selected full-time housewives and their husbands who could benefit from the ESWDC program according to the authors observation - and three different instruments were used in this study. The instruments were administered on 30 respondents in each set. Field observation revealed that many of the women in the State were living in abject poverty thus validating their need for empowerment. Eight different skills are taught at the Centre with the admission requirements being flexible and accessible to any woman. Acquisition of these skills possessed the potentials to alleviate poverty among the women. While most of the full-time housewives demonstrated their willingness to participate in the training programmes of the Centre, their husbands felt contrary and served as a disincentive to their wives. Sustainable strategies capable of circumventing the identified disincentives and build economic resilience in the women were prescribed.